Portugal: EU Issue Voting in Mainstream and Challenger Parties - Lobo, Marina Costa (2023)
One of the “bailout countries” during the Great Recession, Portugal is an interesting case-study to analyse EU politicisation and its effects at the national level. In this chapter, media, parliamentary and voting data provide a comprehensive picture of the role of EU politicisation in Portuguese political behaviour. Trends of EU issue politicisation are presented using salience and tone in mainstream media and parliamentary debates from 2002 to 2019. As expected, the post-2009 period exhibits an increase in politicisation both in media and parliamentary debates. Yet, in a post-bailout stage, and especially since the left coalition government took office in 2015, a degree of depoliticization of the EU issue is detected, with tone improving among the left parties in Parliament. A comprehensive vote model is then set up, using data from a post-2019 election online survey, to examine the degree to which EU issue voting matters, benchmarking with other political issues which were deemed relevant in the election. EU issue voting occurs among Communists but also for the PSD—signalling its importance not only for challenger but also for mainstream parties. Moreover, it matters more than the other socio-economic political issues included in the model.